Respuesta :
Note: Maybe you either forgot to mention the slope or forgot to mention another point from which the equation of the line passes.
In the later part, I would assume the slope m = 2 as an example.
Answer:
Please check the explanation.
Step-by-step explanation:
Given
- The point (-4, -2)
The point-slope form:
The point-slope form of the line equation is defined as
[tex]y-y_1=m\left(x-x_1\right)[/tex]
where
- m is the slope of the line
- (x₁, y₁) is the point
In our case:
(x₁, y₁) = (-4, -2)
substituting the point (-4, -2) in the point-slope form of the equation of the line
[tex]y-y_1=m\left(x-x_1\right)[/tex]
[tex]y-\left(-2\right)=m\left(x-\left(-4\right)\right)[/tex]
Therefore, the point-slope form of the equation of the line using the point (-4,-2) will be:
- [tex]y-\left(-2\right)=m\left(x-\left(-4\right)\right)[/tex]
BONUS!
Example Solving with assuming the slope m = 2
Let suppose the slope m = 2
As we have already got the equation in the point-slope form
[tex]y-\left(-2\right)=m\left(x-\left(-4\right)\right)[/tex]
substituting m = 2
[tex]y-\left(-2\right)=2\left(x-\left(-4\right)\right)[/tex]
[tex]y+2=2\left(x+4\right)[/tex]
Subtract 2 from both sides
[tex]y+2-2=2\left(x+4\right)-2[/tex]
[tex]y=2x+6[/tex]
Thus, the point-slope form of the equation of the line using the point (-4,-2) and having slope m = 2.